2022
DOI: 10.3390/vetsci10010010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Behavior in Beef Cattle: The Physiology, Assessment and Future Directions—A Review

Abstract: Bovine maternal behavior is known to be influenced by a variety of factors including hormonal mediation, breed, age, parity, host genetics and general management practices. Following centuries of varying levels of domestication processes, the behavior of the bovine cow has altered from that of her original wild ungulate ancestors, although many maternal instincts have remained unchanged. The influence of maternal behavior on calf health and performance is of interest to cow-calf beef production operations, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 149 publications
0
8
0
Order By: Relevance
“…Maternal care is a series of species-specific behavioral patterns to ensure the offspring’s survival [ 78 ]. They include interactions such as nursing, attention, and protection of the neonate [ 20 ].…”
Section: The Role Of Oxt In the Establishment Of Maternal Behavior Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal care is a series of species-specific behavioral patterns to ensure the offspring’s survival [ 78 ]. They include interactions such as nursing, attention, and protection of the neonate [ 20 ].…”
Section: The Role Of Oxt In the Establishment Of Maternal Behavior Re...mentioning
confidence: 99%
“…According to the species in question, the results can be variable regarding the function of the OXT. Although OXT and other biomarkers such as PRL, AVP, or cortisone are used to study maternal behavior, some limitations exist [ 78 ], as Ogi et al [ 7 ] reported in 25 Labrador Retriever dogs. They found no association between salivary OXT levels and maternal behaviors, except for sniffing or poking the newborn.…”
Section: The Role Of Oxt In the Establishment Of Maternal Behavior Re...mentioning
confidence: 99%
“…This gene is responsible for the synthesis of dopamine, essential for a healthy pregnancy (Gratz et al, 2018). Dopamine is a key modulator of maternal behavior in rodents, partly because it inhibits the pituitary release of prolactin which modulates lactation, corpora lutea function (in certain species), and maternal behavior (Nevard et al, 2022).…”
Section: Heterogeneous Effects Of Pregnancy On the Expression Profile...mentioning
confidence: 99%
“…Breed differences seem to exist for dopamine secretion, with significantly higher levels in Simmental compared to Brahman and Nguni cattle [111]. The neurotransmitters noradrenaline, dopamine, and serotonin are involved in maternal behaviour in non-bovine species [112]. However, the role of neurotransmitters and their interplay with other hormones around the time of parturition in dairy cows is currently unknown.…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…Instead, Coria-Avila et al [59] showed that maternal behaviour (e.g., licking and nursing) is evoked by changes in the progesterone-estradiol (P4/E2) ratio, and by the oxytocin concentration. Besides progesterone and estradiol, the hormones oxytocin and prolactin are crucial to regulating maternal behaviour during the periparturient period [112]. Oxytocin is secreted from the posterior pituitary gland of the brain, while prolactin is produced by the anterior pituitary gland.…”
Section: Molecular Biomarkersmentioning
confidence: 99%